2003
DOI: 10.1046/j.1466-822x.2003.00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Uphill shifts in distribution of butterflies in the Czech Republic: effects of changing climate detected on a regional scale

Abstract: Aim To assess whether altitude changes in the distribution of butterflies during the second half of the 20th century are consistent with climate warming scenarios. Location The Czech Republic. Methods Distributional data were taken from a recent butterfly distribution atlas, which maps all Czech butterflies using a grid of 10′ longitude to 6′ latitude, equivalent to about 11.1 × 12 km. Cell altitude was used as an independent variable, and altitudinal ranges of individual species (less migrants, extinct specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
115
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(138 citation statements)
references
References 32 publications
10
115
1
2
Order By: Relevance
“…The main trends in the changes are also in line with observed trends in the distribution of wild animals, also explained by climate change, such as certain butterfly species [79] expanding their range to higher elevations. Reference [80] showed that the trend in ongoing changes in bird population sizes and the shifts in nesting areas in the Czech Republic, in the context of climate change, are caused by a decline in species adapted to colder climates in mountainous areas, and an increase in the ranges of lower-elevation species.…”
Section: Discussionsupporting
confidence: 80%
“…The main trends in the changes are also in line with observed trends in the distribution of wild animals, also explained by climate change, such as certain butterfly species [79] expanding their range to higher elevations. Reference [80] showed that the trend in ongoing changes in bird population sizes and the shifts in nesting areas in the Czech Republic, in the context of climate change, are caused by a decline in species adapted to colder climates in mountainous areas, and an increase in the ranges of lower-elevation species.…”
Section: Discussionsupporting
confidence: 80%
“…Similar patterns have emerged for some butterflies in the Czech Republic [64] and Spain [65], vegetation in the Alps [66], and some birds in Southeast Asia [67].…”
Section: Climate Change Effects On Geographic Distribution and Extentsupporting
confidence: 65%
“…The results of this research (Figures 2-4) relating to the predicted changes in forest structure agree with the predictions of impacts of future forest structure on forest animals' mountain habitats (e. g. Konvička et al 2003;Reif et al 2008). The structure and dynamics of managed and unmanaged Norway spruce forests have long been of interest to European foresters and the subject of many ecological studies (Kulhavý 2004).…”
Section: A B C D Esupporting
confidence: 86%